Factors Associated with Chlamydia Infection among Female Sex Workers in West Jakarta: Analysis of the 2018-2019 Integrated Biological and Behavioral Survey - Karamy, Selma Eliana; Sudaryo, Mondastri Korib (Jurnal Epidemiologi Kesehatan Komunitas, 2024)
Background: Chlamydia is one of the most common sexually transmitted infections globally. Female sex workers (FSW), especially in urban areas, face a higher risk of infection due to their risky work environment and lifestyle. Jakarta is a city that has cosmopolitan and urban characteristics with an active sex industry. This research was conducted to determine the factors associated with the incidence of chlamydia infection among FSWs in West Jakarta.Methods: The research was conducted using a cross-sectional design by analyzing data from the 2018-2019 Integrated Biological and Behavioral Survey (IBBS). The data were analyzed using univariate and bivariate analysis with the chi-square test. Prevalence ratio (PR) was used as the measure of association.Results: Of the 283 FSWs involved in the study, the positivity rate of chlamydia infection in West Jakarta reached 42.8%. Significant risk factors for chlamydia infection among FSWs in West Jakarta include younger age, divorced status, recently becoming a sex worker, and having ≥ 5 customers per week.Conclusion: The high rate of chlamydia infection among FSWs in West Jakarta highlights the need to increase outreach to FSWs in order to educate them about STIs and encourage them to perform regular screenings, especially for young FSWs.